Experimental transfusion of variant CJD-infected blood reveals previously uncharacterised prion disorder in mice and macaque. Issue 1 (December 2017) - Comoy, Emmanuel; Mikol, Jacqueline; Jaffré, Nina; Lebon, Vincent; Levavasseur, Etienne; Streichenberger, Nathalie; Sumian, Chryslain; Perret-Liaudet, Armand; Eloit, Marc; Andreoletti, Olivier; Haïk, Stéphane; Hantraye, Philippe; et al.
Abstract Exposure of human populations to bovine spongiform encephalopathy through contaminated food has resulted in <250 cases of variant Creutzfeldt–Jakob disease (vCJD). However, more than 99% of vCJD infections could have remained silent suggesting a long-term risk of secondary transmission particularly through blood. Here, we present experimental evidence that transfusion in mice and non-human primates of blood products from symptomatic and non-symptomatic infected donors induces not only vCJD, but also a different class of neurological impairments. These impairments can all be retransmitted to mice with a pathognomonic accumulation of abnormal prion protein, thus expanding the spectrum of known prion diseases. Our findings suggest that the intravenous route promotes propagation of masked prion variants according to different mechanisms involved in peripheral replication. It is hypothesised that exposure to bovine spongiform encephalopathy through contaminated food could have resulted in a large proportion of latent variant Creutzfeldt-Jakob disease cases in humans. Here the authors demonstrate that inoculation with blood from non-symptomatic, vCJD infected humans, results in a unique prion-like disorder in mice and macaques.